2010
DOI: 10.1161/hypertensionaha.110.152207
|View full text |Cite|
|
Sign up to set email alerts
|

Heparin Cofactor II Protects Against Angiotensin II-Induced Cardiac Remodeling Via Attenuation of Oxidative Stress in Mice

Abstract: Abstract-Heparin cofactor II (HCII), a serine protease inhibitor, inhibits tissue thrombin action after binding with dermatan sulfate proteoglycans in the extracellular matrix of the vascular system. We previously reported that heterozygous HCII-deficient (HCII ϩ/Ϫ ) humans and mice demonstrate acceleration of vascular remodeling, including atherosclerosis. However, the action of HCII on cardiac remodeling never has been determined. HCII ϩ/ϩ and HCII ϩ/Ϫ mice at age 25 weeks were infused with angiotensin II (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Another beneficial effect of paricalcitol is that it activates both antihypertrophic and antifibrotic activity in a murine model of cardiac hypertrophy and fibrosis generated by chronic infusion of ANG II (7,15,43). Accordingly, in our model, animals given paricalcitol showed significant reductions in heart/body weight ratios compared with other diabetic animals.…”
Section: Discussionmentioning
confidence: 64%
“…Another beneficial effect of paricalcitol is that it activates both antihypertrophic and antifibrotic activity in a murine model of cardiac hypertrophy and fibrosis generated by chronic infusion of ANG II (7,15,43). Accordingly, in our model, animals given paricalcitol showed significant reductions in heart/body weight ratios compared with other diabetic animals.…”
Section: Discussionmentioning
confidence: 64%
“…In experimental animal studies, we and Vicente et al revealed that HCII-deficient mice showed more prominent intimal hyperplasia after vascular injury than did in wild-type (WT) littermates (11,12). In addition, plasma HCII activity is inversely associated with acceleration of human and murine cardiac remodeling including atrial enlargement and left ventricular concentric alteration (13,14). These findings revealed that HCII plays a protective role in the development of vascular remodeling and cardiac remodeling in humans and mice.…”
Section: Heparin Cofactor II (Hcii)mentioning
confidence: 79%
“…HCII ϩ/Ϫ mice were backcrossed for 10 generations with the C57BL/6J strain (12). Because our homozygote HCIIdeficient mice were embryonically lethal, we used male heterozygote HCII-deficient (HCII ϩ/Ϫ ) mice and male littermate WT (HCII ϩ/ϩ ) mice in all experiments of this study as in our previous studies (12,14). Our HCII ϩ/Ϫ mice showed approximately half of the plasma HCII activity of littermate WT mice, and there is no obviously different phenotype in either HCII ϩ/ϩ mice or HCII ϩ/Ϫ mice at base line (12).…”
Section: Methodsmentioning
confidence: 99%
“…41 In that study, infusion of angiotensin II prominently accelerated cardiac remodeling, including concentric LV changes, enlargement of LAV and exaggeration of cardiac fibrosis in HCII-deficient mice when compared with littermate wild-type mice. 41 The study using HCII-deficient mice demonstrated that HCII protects against angiotensin II-induced cardiac remodeling through the suppression of the NAD(P)H oxidase-TGF-b1 pathway. 41 Therefore, we speculate that HCII is also capable of attenuating oxidative stress in the human heart, as well as in the murine heart through suppression of the NAD(P)H oxidase-TGF-b1 pathway.…”
Section: Discussionmentioning
confidence: 87%
“…41 The study using HCII-deficient mice demonstrated that HCII protects against angiotensin II-induced cardiac remodeling through the suppression of the NAD(P)H oxidase-TGF-b1 pathway. 41 Therefore, we speculate that HCII is also capable of attenuating oxidative stress in the human heart, as well as in the murine heart through suppression of the NAD(P)H oxidase-TGF-b1 pathway.…”
Section: Discussionmentioning
confidence: 99%